2011
DOI: 10.1103/physrevb.83.115457
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectrum of the endohedralY2C2@C

Abstract: The structure and vibrational spectrum of the novel endohedral fullerene Y2C2@C92 was studied by Raman spectroscopy, with particular emphasis on the rotational transitions of the diatomic C2 unit in the low energy Raman spectrum. We report evidence for tunneling of this unit through the C2 rotation plane and observe anomalous narrowing in a hindered rotational mode. We also report complementary density functional theory (DFT) calculations that support our conclusions and discuss potential applications to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…For other rare earth metal elements, CCMFs are also common, but a size effect occurs due to the strong interactions between the metallic cluster and the cage (Figure ). A thorough inspection of the reported compounds with a composition of M 2 C 2 @C 2 n reveals that the small Sc 2 C 2 cluster prefers to be encapsulated inside the cages smaller than C 88 , but the relatively large M 2 C 2 (M = Gd, Tb, and Y) clusters tend to choose either the non-isolated pentagon rule (non-IPR) C 1 (51383)-C 84 cage or the even larger D 3 (85)-C 92 cage. These results indicate that the size matching between the encapsulated metallic cluster and the fullerene is an important factor determining the stability of the resultant EMFs.…”
Section: Bonding Inside Emfsmentioning
confidence: 99%
“…For other rare earth metal elements, CCMFs are also common, but a size effect occurs due to the strong interactions between the metallic cluster and the cage (Figure ). A thorough inspection of the reported compounds with a composition of M 2 C 2 @C 2 n reveals that the small Sc 2 C 2 cluster prefers to be encapsulated inside the cages smaller than C 88 , but the relatively large M 2 C 2 (M = Gd, Tb, and Y) clusters tend to choose either the non-isolated pentagon rule (non-IPR) C 1 (51383)-C 84 cage or the even larger D 3 (85)-C 92 cage. These results indicate that the size matching between the encapsulated metallic cluster and the fullerene is an important factor determining the stability of the resultant EMFs.…”
Section: Bonding Inside Emfsmentioning
confidence: 99%
“…The BWF interference effect involving the interactions of discrete phonon states and the electronic continuum has been studied extensively in carbon-based materials (graphite, graphene, and nanotubes) [49][50][51] and semiconductors. [52][53][54][55] However, there are limited reports of this effect in TMDs. This electron-phonon interaction effect manifests itself as an asymmetric broadening in the phonon line shape depending on the dopant (p-doped or n-doped) and is described by the asymmetric parameter (1/q BWF ).…”
Section: Resonance Effect: Bwf Interference Effectmentioning
confidence: 99%
“…It is known that the BWF asymmetric parameter is dependent on carrier concentration. Extensive research has been reported on doped porous silicon 55,59,60 and other bulk semiconducting materials. 52,53 Recently, the effect of doping on the electronic transport and phonon line shapes of TMDs has been reported experimentally 56,61,62 and theoretically.…”
Section: Effect Of Carrier Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Its carbide nature was later further confirmed by the same group utilizing 13 C NMR combined with synchrotron X-ray structural studies. Likewise, di-EMFs based on the groups III and IV metal atoms, to date, have achieved excellent progress, for instance, Er 2 C 2 @C 82 , Gd 2 C 2 @C 2 n (2 n = 88–92), , Y 2 C 2 @C 2 n (2 n = 82, 84, 92, 100), Ti 2 C 2 @C 78 , Dy 2 C 2 @C 82 , Tm 2 C 2 @C 82 , Tb 2 C 2 @C 82 , Sc 2 C 2 @C 82 and mixed metal carbide clusterfullerene ErYC 2 @C 82 , all of which are proven to be CCFs. An increasing number of facts have proved that much attention to the structural determination of di-EMFs with large carbon cages should be paid, such as Ti 2 C 80 , Sc 2 C 82 , and so on, in that their simple endohedral forms M 2 @C n may not fulfill the stable geometry structure and closed-shell electronic configuration rule (CSECR).…”
Section: Introductionmentioning
confidence: 99%